2015
DOI: 10.1097/nmd.0000000000000388
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Mental Health Problems Among Orphaned Children and Adolescents in Tanzania

Abstract: Low- and middle-income countries (LMIC) have a high number of orphans, many of whom have unmet mental health needs. Effective mental health interventions are needed; however, it is necessary to understand how mental health symptoms and needs are perceived locally in order to tailor interventions and refine measurement of intervention effects. We used an existing rapid ethnographic assessment approach to identify mental health problems from the perspective of orphans and guardians to inform a subsequent randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 34 publications
3
38
0
Order By: Relevance
“…Low somatization may reflect internalizing negative cognitions and effects, contrary to the typical interpersonal expression of distress, albeit somatic, for females. As with previous studies, our findings showed higher levels of social stress predicted previous suicide attempt (Blum et al, 2003;Dorsey et al, 2015;Hagaman et al, 2013;Shilubane et al, 2012). Adult-led engagement and interpersonal skills training for internalizing problems may benefit high-risk females in LMIC settings (Kapur, House, May, & Creed, 2003).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Low somatization may reflect internalizing negative cognitions and effects, contrary to the typical interpersonal expression of distress, albeit somatic, for females. As with previous studies, our findings showed higher levels of social stress predicted previous suicide attempt (Blum et al, 2003;Dorsey et al, 2015;Hagaman et al, 2013;Shilubane et al, 2012). Adult-led engagement and interpersonal skills training for internalizing problems may benefit high-risk females in LMIC settings (Kapur, House, May, & Creed, 2003).…”
Section: Discussionsupporting
confidence: 87%
“…Adult-led engagement and interpersonal skills training for internalizing problems may benefit high-risk females in LMIC settings (Kapur, House, May, & Creed, 2003). As with previous studies, our findings showed higher levels of social stress predicted previous suicide attempt (Blum et al, 2003;Dorsey et al, 2015;Hagaman et al, 2013;Shilubane et al, 2012). The absence of communication about thoughts of suicide, distress, and hopelessness are common in low-income settings, especially among orphans (Fleischmann et al, 2008;Keys, Kaiser, Kohrt, Khoury, & Brewster, 2012).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This could reflect mounting pressures on control students not shared by intervention students. For instance, difficulty paying secondary school fees is a major source of stress for orphaned students in low‐income countries that can accumulate over time (Cluver et al., ; Dorsey et al., ). It is possible that control students experienced increasing stress as they struggled to remain enrolled, whereas intervention students were spared this particular stressor due to the education guarantees of the program.…”
Section: Discussionmentioning
confidence: 99%